2018
DOI: 10.1101/303412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic evaluation of isoform function in literature reports of alternative splicing

Abstract: Though most genes in mammalian genomes have multiple isoforms, an ongoing debate is whether these isoforms are all functional as well as the extent to which they increase the functional repertoire of the genome. Here we present a literature-based analysis of experimental evidence for functionally distinct splice isoforms (FDSIs), that is, the gene has multiple splice isoforms necessary for the gene's overall function. We established a curation framework for evaluating experimental evidence of FDSIs, and analyz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…promote apoptosis vs. cell proliferation, act as dominant negatives, etc.) [51][52][53]. Moreover, large-scale analyses of protein-protein interactions revealed that a large fraction of exon skipping events modulate interactions with specific partners, leading to the rewiring of interaction networks [54][55][56].…”
Section: 2) Exon Skipping-rich Transcriptomes In Bilateriansmentioning
confidence: 99%
“…promote apoptosis vs. cell proliferation, act as dominant negatives, etc.) [51][52][53]. Moreover, large-scale analyses of protein-protein interactions revealed that a large fraction of exon skipping events modulate interactions with specific partners, leading to the rewiring of interaction networks [54][55][56].…”
Section: 2) Exon Skipping-rich Transcriptomes In Bilateriansmentioning
confidence: 99%
“…For genes with multiple exons in the human genome, 95% are alternatively spliced [2] . AS is an important transcriptional regulation mechanism that increases the structural and functional diversity of gene products [3,4] . Several studies have found that AS is associated with cancers and other complex diseases [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%